Optimization of the cultivation conditions of Bacillus licheniformis BCLLNF-01 for cellulase production - Raquel Nascimento da Silva; Liany Figuerêdo de Andrade Melo; Christine Lamenha Luna Finkler (Biotechnology Reports, 2021)
The objective of this study was to optimize the production of CMCase by Bacillus licheniformis BCLLNF-01, a strain associated with the mucus of the zoanthid Palythoa caribaeorum (Cnidaria, Anthozoa). Production of total cellulase and CMCase was investigated in the supernatant, intracellular content and wall content. Cultivation was carried out in BLM medium supplemented with 1.5 % (w/v) CMC, 5.5 % (v/v) inoculum, 40 °C, pH 6.5, 500 rpm for 72 h, and the highest activity was recorded in the supernatant. A Rotational Central Composite Design (RCCD) 2³ was used to investigate the influence of the carbon source concentration (CMC-0.5 to 1.5 % w/v), inoculum concentration (1–10 % v/v) and temperature (35–45 °C) on CMCase production. The maximum enzyme activity was achieved for a CMC concentration of 1.5 % w/v at 40 °C, attaining 0.493 IU/mL after 96 h of cultivation.